Encounters with death: was there dark tourism in Classical Greece? - Sulosky Weaver, Carrie L. (Journal of Greek Archaeology, 2016)
‘Dark tourism’ is generally defined as travel to sites associated with suffering, death, or the macabre. In the modern world, popular dark tourism destinations include bloody battlefields such as Gallipoli and Waterloo, sites of disaster like Chernobyl and the World Trade Center, and scenes of genocide including the Holocaust concentration camps and the killing fields of Rwanda. Although some scholars in the burgeoning field of dark tourism studies maintain that travel of this sort is a phenomenon of the late 20th and early 21st centuries, humans have long been drawn to places of death and disaster, and dark tourism arguably has its roots in antiquity.